Facemasks for prevention of viral respiratory infections in community settings: A systematic review and meta-analysis - Nishant Aggarwal; Vignesh Dwarakanathan; Nitesh Gautam; Animesh Ray (Wolters Kluwer Medknow Publications, 2020)
Background: There is paucity of evidence on the effectiveness of facemask use in COVID-19 in community settings. Objectives: We aimed to estimate the effectiveness of facemask use alone or along with hand hygiene in community settings in reducing the transmission of viral respiratory illness. Methods: We searched PubMed and Embase for randomized controlled trials on facemask use in community settings to prevent viral respiratory illnesses published up to April 25, 2020. Two independent reviewers were involved in synthesis of data. Data extraction and risk-of-bias assessment were done in a standard format from the selected studies. Outcome data for clinically diagnosed or self-reported influenza-like illness (ILI) was recorded from individual studies. Pooled effect size was estimated by random-effects model for "facemask only versus control" and "facemask plus hand hygiene versus control." Results: Of the 465 studies from PubMed and 437 studies from Embase identified from our search, 9 studies were included in qualitative synthesis and 8 studies in quantitative synthesis. Risk of bias was assessed as low (n = 4), medium (n = 3), or high (n = 1) risk. Interventions included using a triple-layered mask alone or in combination with hand hygiene. Publication bias was not significant. There was no significant reduction in ILI either with facemask alone (n = 5, pooled effect size: −0.17; 95% confidence interval [CI]: −0.43-0.10; P = 0.23; I2 = 10.9%) or facemask with handwash (n = 6, pooled effect size: (n=6, pooled effect size: −0.09; 95% CI: -0.58 to 0.40; P = 0.71, I2 = 69.4%). Conclusion: Existing data pooled from randomized controlled trials do not reveal a reduction in occurrence of ILI with the use of facemask alone in community settings.